Evaluation of hypertension and diabetes risk factors and the effects of Omega-3 fatty acids and vitamin C on inflammatory markers in hypertensive and diabetic obese adults in Palestine - Ellulu, Mohammed S. S. (2015)
Obesity or an increase in body adiposity has been envisaged by WHO as the fifth leading risk of global deaths. It was well associated with metabolic disorders as hypertension (HT) and type-2 diabetes (T2DM). Adipose tissue plays an active role in endocrine function by secreting adipokines that involve inflammatory and anti-inflammatory cytokines. A cross-sectional study involved 484 adult subjects in seven primary healthcare centers in Gaza City, Palestine, was carried out to determine whether the alteration of inflammatory indicators was associated with obesity and/or disease conditions. After that, 108 obese patients of HT and/or T2DM were selected from the cross-sectional part and assigned into three equal groups (each group 36 patients); Control, Vitamin C (1 gram/daily), and Omega-3 FAs (0.5 gram/daily) via a randomized controlled trial (RCT); in order to identify the effects of intervention factors on inflammatory and metabolic markers. The results of cross-sectional part indicated that obesity was the main risk factor associated with alteration of Adiponectin, C reactive protein (CRP), and interleukin 6 (IL-6). Uncontrolled HT and T2DM were also risk factors associated with Adiponectin and CRP alteration. In the RCT part, balance was achieved between the groups and the confounders were neutralized at the randomization time. 95 (88%) patients were completed to final analysis. Within Vitamin C group, the significant reductions (P˂0.05) were detected for CRP [from 14.86±9.20 to 7.74±4.53 mg/L], IL-6 [from 2.20±0.75 to 1.40±0.53 pg/mL], fasting blood glucose (FBG) [from 188.13±81.24 to 126.16±34.06 mg/dL], and triglyceride (TG) [from 223.81±87.88 to 155.10±48.12 mg/dL]. Within Omega-3 FAs group, the significant changes (P˂0.05) were detected for CRP [from 14.78±10.73 to 8.49±6.69 mg/L], FBG [from 178.13±58.5 to 157.32±59.7 mg/dL], and TG [from 209.23±108.3 to 167.0±79.9 mg/dL]. Within control group, the significant changes (P˂0.05) were detected for FBG [from 187.15±64.8 to 161.91±37.9mg/dL] and TG [from 202.91±107.0 to 183.45±95.82 mg/dL]. In conclusion, at the endpoint, repeated comparisons between the groups detected the efficacy of Vitamin C on CRP, IL-6, and FBG, meaning that Vitamin C supplementation has treating effects while Omega-3 FAs supplementation has protective effect.